2016
DOI: 10.1371/journal.pone.0150100
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Immunity with Rotavirus Vaccine Immunogenicity in Zambian Infants

Abstract: IntroductionLive attenuated oral vaccines against rotavirus (RV) have been shown to be less efficacious in children from developing countries. Reasons for this disparity are not fully understood. We assessed the role of maternal factors including breast milk RV-specific IgA, transplacentally acquired infant serum RV-specific IgG and maternal HIV status in seroconversion among Zambian infants routinely immunized with Rotarix™ (RV1).Methods420 mother-child pairs were recruited at infant age 6–12 weeks in Lusaka.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
60
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 37 publications
(43 reference statements)
4
60
0
4
Order By: Relevance
“…If natural exposure precedes vaccination, this may induce systemic and/or local immunity that impairs vaccine immunogenicity. In the case of rotavirus, exposure to natural infection in the neonatal period is common in settings with a high transmission intensity, and appears to be greatest at times of year associated with impaired vaccine immunogenicity [23]. In a review of Rotarix trials, baseline rotavirus-specific IgA seropositivity (indicative of prior virus exposure) was rare in studies performed in Europe and North America but was observed in up to 26% of participants in higher-burden settings [174].…”
Section: Transmission Intensity and Strain Diversity Of The Infectious mentioning
confidence: 99%
See 3 more Smart Citations
“…If natural exposure precedes vaccination, this may induce systemic and/or local immunity that impairs vaccine immunogenicity. In the case of rotavirus, exposure to natural infection in the neonatal period is common in settings with a high transmission intensity, and appears to be greatest at times of year associated with impaired vaccine immunogenicity [23]. In a review of Rotarix trials, baseline rotavirus-specific IgA seropositivity (indicative of prior virus exposure) was rare in studies performed in Europe and North America but was observed in up to 26% of participants in higher-burden settings [174].…”
Section: Transmission Intensity and Strain Diversity Of The Infectious mentioning
confidence: 99%
“…In a review of Rotarix trials, baseline rotavirus-specific IgA seropositivity (indicative of prior virus exposure) was rare in studies performed in Europe and North America but was observed in up to 26% of participants in higher-burden settings [174]. A reduction in vaccine immunogenicity among infants positive for rotavirus-specific IgA was recently observed during studies of Rotarix conducted in Zambia [23], Bangladesh [135] and South Africa [36], but not in India [175]. Pre-vaccination exposure seems to have a similar effect on the immunogenicity of oral cholera vaccines, including both live-attenuated [11,93,176] and inactivated vaccines [96,177,178].…”
Section: Transmission Intensity and Strain Diversity Of The Infectious mentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is consistent evidence from clinical trials that RV have lower efficacies in low-and middle-income countries (LMIC): vaccine efficacies are 80 to 90% in high-income countries (HIC) and 40 to 60% in LMIC (3-8). Indeed, there is growing evidence from vaccine effectiveness studies emerging from the field that in real-life use, vaccine effectiveness is also consistently lower in LMIC (9-12).In addition to the differences in observed vaccine efficacy and effectiveness, there are also marked differences in vaccine-elicited immunity as reported by various vaccine-elicited antibody titers following rotavirus immunization (13)(14)(15)(16)(17)(18). A number of hypotheses have been put forward to explain the differences in efficacy and vaccineelicited immunity between HIC and LMIC.…”
mentioning
confidence: 99%